ANALISIS KEMAMPUAN PENALARAN MATEMATIKA DITINJAU DARI SELF-EFFICACY SISWA SEKOLAH DASAR INKLUSI - Abiyyu Arhab Hanan; Danuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of self-efficacy on the mathematical reasoning ability of inclusive elementary school students in Cluster III, Kasihan District, Bantul Regency. This research employed a quantitative approach with a correlational research design. The population consisted of all inclusive elementary school students in Cluster III Kasihan Bantul, with a sample of 105 students selected using purposive sampling technique. Data were collected through a self-efficacy questionnaire and a mathematical reasoning ability test. The obtained data were analyzed using descriptive statistics and simple linear regression analysis with the assistance of IBM SPSS Statistics. The results indicated that self-efficacy had a significant effect on students' mathematical reasoning ability. This was indicated by a significance value of 0.005, which is smaller than 0.05. In addition, the coefficient of determination (R²) value of 0.075 indicates that self-efficacy contributes 7.5% to students’ mathematical reasoning ability. These findings suggest that students’ confidence in their ability to complete mathematical tasks can support the development of their mathematical reasoning skills. However, mathematical reasoning ability is also influenced by other factors such as conceptual understanding of mathematics, learning strategies applied by teachers, and students’ learning experiences in solving mathematical problems.